The Authority of the Court in Deciding Cases that Choose Foreign Law as a Choice of Law - Khairunnisa, Verina; Azheri, Busyra; Anggunsuri, Upita (Andalas Law Journal, 2025)
Choice of law is one of the clauses in contracts that arise due to economic globalization. The use of this choice of law has led to the question of which forum has the right to resolve disputes if the agreement does not include a choice of forum. This research will analyze the jurisdiction of which court has the authority to adjudicate when the contract is subject to foreign law and the legal consequences if there is a choice of foreign law. The method used in this research is normative juridical with an emphasis on literature study. The results of this study concluded that the Central Jakarta District Court is not authorized to adjudicate disputes in which the agreement chooses English law as the choice of law because England uses a common law legal system which defines the choice of law as well as the choice of forum so that the settlement of the case must be carried out in the English Court. The legal consequences arising from the making of a contract that is subject to foreign law are the rights and obligations that are regulated in accordance with the chosen law.